Morphological features of translation from English into Uzbek - O'ktamova, Mokhigul; Akramova, Dilnoza (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article is devoted to the analysis of morphological features in the process of translation from English into Uzbek. The study examines the differences between the morphological systems of the English and Uzbek languages, with particular attention to grammatical categories, parts of speech, affixation, and the rendering of grammatical forms in translation. The analytical nature of English and the agglutinative structure of Uzbek require morphological adaptation during the translation process. The article analyzes the transfer of verb tenses, voice, and person-number categories into Uzbek through illustrative examples. The findings emphasize the importance of maintaining morphological equivalence and preserving semantic accuracy in translation. The study contributes to the development of translation theory and practice.